2011
DOI: 10.1016/j.beproc.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Domain independence and stability in young and older adults’ discounting of delayed rewards

Abstract: Individual discounting rates for different types of delayed reward are typically assumed to reflect a single, underlying trait of impulsivity. Recently, we showed that discounting rates are orders of magnitude steeper for directly consumable liquid rewards than for monetary rewards (Jimura et al. 2009), raising the question of whether discounting rates for different types of reward covary at the individual level. Accordingly, the present study examined the relation between discounting of hypothetical money and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
180
2
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(207 citation statements)
references
References 17 publications
13
180
2
9
Order By: Relevance
“…selection of food or social exchange. This possibility seems very likely in light of research pointing to an absence of mutual correlations between the rate of discounting of various types of delayed rewards (Jimura et al, 2011). Positive relationship between the rate of discounting in various domains may result from the fact that discounting in the both considered domains is under influence of the third variable, e.g.…”
Section: Fig 1 Payoff Matrix Of 2-person Prisoner's Dilemma Game (Pmentioning
confidence: 99%
“…selection of food or social exchange. This possibility seems very likely in light of research pointing to an absence of mutual correlations between the rate of discounting of various types of delayed rewards (Jimura et al, 2011). Positive relationship between the rate of discounting in various domains may result from the fact that discounting in the both considered domains is under influence of the third variable, e.g.…”
Section: Fig 1 Payoff Matrix Of 2-person Prisoner's Dilemma Game (Pmentioning
confidence: 99%
“…Many prior studies find either stability (Green et al, 1996;Chao et al, 2009) or reductions in discounting across adult age (Green et al, , 1999Harrison et al, 2002;Reimers et al, 2009;Jimura et al, 2011;Löcken-hoff et al, 2011), but others have reported increases in discounting from young adulthood to older age (Read and Read, 2004). Overall, the existing behavioral literature is conflicting.…”
Section: Proportion Of Later Choicesmentioning
confidence: 99%
“…This approach has produced theories asserting that delay discounting (i.e., the preference for sooner, smaller rewards relative to larger, later rewards) should decline with age (Rogers, 1994), increase with age (Trostel and Taylor, 2001), or be minimized in middle age (Read and Read, 2004). Empirical results from psychology and behavioral economics are similarly conflicting (Green et al, , 1996(Green et al, , 1999Harrison et al, 2002;Read and Read, 2004;Chao et al, 2009;Reimers et al, 2009;Whelan and McHugh, 2009;Jimura et al, 2011;Löckenhoff et al, 2011). One important potential contribution to models of intertemporal choice over the life span, which has been overlooked to date, may be that older and younger adults rely differently on the brain systems that underlie valuation of future outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chapman (1996) has reported that rates of discounting monetary and health rewards are uncorrelated. Moreover, Jimura et al (2009Jimura et al ( , 2011 in a series of experiments showed that the correlation between discounting of liquid and monetary rewards was not significant, providing evidence that these two reward domains are independent at the individual level. Interesting, in the same experiments (Jimura et al 2011) individual differences in discounting of both reward types were stable over several weeks.…”
Section: Discounting As a Personality Traitmentioning
confidence: 99%
“…Moreover, Jimura et al (2009Jimura et al ( , 2011 in a series of experiments showed that the correlation between discounting of liquid and monetary rewards was not significant, providing evidence that these two reward domains are independent at the individual level. Interesting, in the same experiments (Jimura et al 2011) individual differences in discounting of both reward types were stable over several weeks. These results suggest that although similar decision-making processes may be involved, the discounting of one type of rewards and the discounting of other type of rewards reflect separate, temporally stable individual characteristics, rather than a single trait of impulsivity.…”
Section: Discounting As a Personality Traitmentioning
confidence: 99%